A high performance ceramic composite material and preparation method thereof

Through the combination of nanofibers, graphene and ceramic matrix, combined with specific additives and process treatment, the problems of insufficient bending strength, fracture toughness and wear resistance of ceramic composite materials are solved, and the preparation of high-performance ceramic composite materials is realized, simplified Process and reduce costs.

CN118754695BActive Publication Date: 2025-01-07苏州芯合半导体材料有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411244675.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-01-07
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

The existing ceramic composite materials have insufficient flexural strength, fracture toughness and wear resistance, and the preparation process is complex and costly, making it difficult to meet the market's demand for high-performance materials.

Method used

Using a combination of nanofiber materials, graphene, ceramic matrix and other nanomaterials, through specific ratios and preparation processes, high-performance ceramic composite materials are formed, including 15-25 parts of nanofiber materials, 3-5 parts of graphene, and ceramics. 60-80 parts of matrix, 8-12 parts of other nanomaterials, 1-3 parts of additives, and the ceramic matrix is ​​Zr-Al-Ba-Ge-rare earth element-M-Q-O. The additives include amphoteric organic ion salts and benzene ring-containing hyperbranching Polyborsilazane and Meso-tetramethyl-meso-tetrap-aminophenyl cup [4]pyrrole were prepared by hydrothermal reaction and sintering treatment.

Benefits of technology

It significantly improves the bending strength, fracture toughness and wear resistance of ceramic composite materials, simplifies the preparation process, reduces costs, is suitable for continuous large-scale production, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-performance ceramic composite material and a preparation method thereof, and relates to the technical field of composite materials. The composite material comprises the following components by weight: 15-25 parts of nanofiber material, 3-5 parts of graphene, 60-80 parts of ceramic matrix, 8-12 parts of other nanomaterials, and 1-3 parts of auxiliary agent; the ceramic matrix is ​​Zr-Al-Ba-Ge-rare earth element-M-Q-O, wherein M is at least one of Ti, Ta, Hf, and Nb; the Q is a mixture of B and Si in a mass ratio of 1:(0.8-1.2); the auxiliary agent comprises the following raw materials by weight: 3-6 parts of amphoteric organic ion salt, 1-2 parts of benzene ring-containing hyperbranched polyborosilazane, and 0.2-0.4 parts of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole. The material has high flexural strength, sufficient fracture toughness, and good wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a high-performance ceramic composite material and a preparation method thereof. Background Art

[0002] Ceramic composite materials are a new generation of thermal structural materials after metal materials. They are currently a material that is highly valued in the field of materials science. Due to their high melting point, anti-oxidation, anti-corrosion, high temperature resistance and wear resistance, they are widely used in aviation, aerospace, chemical industry, transportation and other fields.

[0003] Traditional ceramic composite materials generally have low bending strength, low fracture toughness, complex preparation process and high preparation cost. Ceramic composite materials on the market also have more or less technical defects such as wear resistance to be further improved. In order to solve the above problems, the Chinese invention patent with application publication number CN117945770A discloses a method for preparing ceramic-based composite materials, including porous CMC preform preparation, slurry preparation, C / SiC-HfC composite intermediate preparation, C / SiC-HfC-C composite intermediate preparation, HfC ceramic precursor preparation, SiC ceramic precursor preparation, and ZrC ceramic preparation process. It also relates to a ceramic-based composite material, including a carbon fiber reinforced phase, a SiC-HfC-ZrC ceramic matrix phase, and the matrix phase is a core-shell structure with HfC as the core and SiC-ZrC as the shell. The ceramic powder slurry introduced in the preparation method of the invention forms an ultra-high temperature component of a core-shell structure in the matrix, which improves the matrix's ablation resistance and has high densification efficiency. The prepared three-phase ceramic matrix composite has excellent mechanical properties, low preparation cost, convenient operation, low energy consumption, and green environmental protection, which greatly shortens the preparation cycle of ceramic matrix composites. However, the flexural strength, fracture toughness and wear resistance of the ceramic composite still need to be further improved.

[0004] It can be seen that the development of a high-performance ceramic composite material with high flexural strength, sufficient fracture toughness and good wear resistance and its preparation method meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the field of ceramic composite materials. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a high-performance ceramic composite material having high bending strength, sufficient fracture toughness and good wear resistance and a preparation method thereof.

[0006] To achieve the above object, the technical scheme adopted by the present invention is: a high-performance ceramic composite material, comprising the following components in parts by weight: 15-25 parts of nanofiber material, 3-5 parts of graphene, 60-80 parts of ceramic matrix, 8-12 parts of other nanomaterials, and 1-3 parts of additives; the ceramic matrix is ​​Zr-Al-Ba-Ge-rare earth element-MQO, wherein M is at least one of Ti, Ta, Hf, and Nb; the Q is B and Si mixed in a mass ratio of 1:(0.8-1.2); the additive comprises the following raw materials in parts by weight: 3-6 parts of amphoteric organic ion salt, 1-2 parts of benzene ring-containing hyperbranched polyborosilazane, and 0.2-0.4 parts of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole.

[0007] Preferably, the amphoteric organic ion salt is at least one of hydroxypropane sulfonate pyridinium salt and 1-benzylpyridine-3-carboxylate.

[0008] Preferably, there is no special requirement for the source of the benzene ring-containing hyperbranched polyborosilazane. In one embodiment of the present invention, the benzene ring-containing hyperbranched polyborosilazane is prepared according to the method in the Chinese invention patent with application announcement number CN117024144A.

[0009] Preferably, the preparation method of the meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole is described in: Guo Yong, Shao Shijun, He Lijun, et al. Synthesis and Characterization of Meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole [J]. Chemical Reagents, 2002(6):344-345.

[0010] Preferably, the rare earth elements are Y, Ce, and Gd mixed in a mass ratio of 1:(1-2):(0.3-0.5).

[0011] Preferably, the other nanomaterials are nano-aluminum nitride, nano-chromium boride, nano-hafnium silicide, and nano-molybdenum carbide mixed in a mass ratio of 1:(1-2):(0.8-1.2):(1-1.5).

[0012] Preferably, the particle size of the other nanomaterials is 20-90 nm.

[0013] Preferably, the preparation method of the ceramic matrix comprises the following steps: dispersing a zirconium source, an aluminum source, a barium source, a germanium source, a rare earth source, an M source, and a Q source in an alcohol solvent, stirring evenly, slowly adding sodium acetate to obtain a mixture, transferring the mixture to a polytetrafluoroethylene-lined hydrothermal reactor, and reacting at 200-220°C for 15-22h; cooling to room temperature, repeatedly washing with anhydrous ethanol, drying to constant weight in a vacuum drying oven at 85-95°C, and grinding through a 300-500 mesh sieve after roasting to obtain a ceramic matrix.

[0014] Preferably, the zirconium source is at least one of zirconium chloride and zirconium nitrate; the aluminum source is at least one of aluminum chloride and aluminum nitrate; the barium source is at least one of barium chloride and barium nitrate; the germanium source is germanium chloride; the rare earth source includes yttrium nitrate, cerium nitrate, and gadolinium chloride; the M source is at least one of titanium nitrate, tantalum ethoxide, hafnium tetranitrate, and niobium pentachloride; and the Q source includes sodium borate and silicon tetrachloride.

[0015] Preferably, the ratio of the zirconium source, aluminum source, barium source, germanium source, rare earth source, M source, Q source, alcohol solvent and sodium acetate is 1:(0.4-0.6):0.05:(0.08-0.12):0.1:0.12:0.03:(10-20):3.

[0016] Preferably, the alcohol solvent is at least one of ethanol, ethylene glycol and n-butanol.

[0017] Preferably, the graphene is a single-layer graphene powder with a flake diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm.

[0018] Preferably, the nanofiber material is at least one of nano-boron fiber and carbon nanofiber.

[0019] Preferably, the nanofiber material has an average diameter of 20-100 nm and a length of 10-30 μm.

[0020] Another object of the present invention is to provide a method for preparing the high performance ceramic composite material, comprising the following steps:

[0021] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0022] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;

[0023] Step S3: sintering the green body to obtain a high-performance ceramic composite material.

[0024] Preferably, the drying in step S2 is carried out under vacuum, the drying time is 15-24 hours, and the drying temperature is 85-95°C.

[0025] Preferably, the screening in step S2 is through a 100-300 mesh sieve; the debinding is carried out in a vacuum environment, the debinding temperature is 440-550°C, and the debinding time is 2-4h; the shaping pressure is 12-18MPa, the temperature is 200-300°C, and the insulation time is 2-3 hours.

[0026] Preferably, the sintering conditions in step S3 are: heating rate 6-10°C / min, sintering temperature 1550-1950°C, and holding time 5-12h.

[0027] Due to the application of the above technical solution, the present invention has the following beneficial effects:

[0028] (1) The preparation method of the high-performance ceramic composite material disclosed in the present invention has simple process, convenient operation and control, high preparation efficiency and finished product qualification rate, low dependence on equipment, suitable for continuous large-scale production, and has high promotion and application value.

[0029] (2) The high-performance ceramic composite material disclosed in the present invention comprises the following components in parts by weight: 15-25 parts of nanofiber material, 3-5 parts of graphene, 60-80 parts of ceramic matrix, 8-12 parts of other nanomaterials, and 1-3 parts of additives; the ceramic matrix is ​​Zr-Al-Ba-Ge-rare earth element-MQO, wherein M is at least one of Ti, Ta, Hf, and Nb; the Q is a mixture of B and Si in a mass ratio of 1:(0.8-1.2); the additive comprises the following raw materials in parts by weight: 3-6 parts of amphoteric organic ion salt, 1-2 parts of benzene ring-containing hyperbranched polyborosilazane, and 0.2-0.4 parts of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole. Through the mutual coordination and joint action of the components, the prepared ceramic composite material has high flexural strength, sufficient fracture toughness, and good wear resistance.

[0030] (3) The high-performance ceramic composite material disclosed in the present invention can form an effective crack deflection and reinforcement effect by rationally selecting the preparation components and their content ratios, thereby effectively improving the bending strength and fracture toughness, thereby extending the service life of the composite material.

[0031] (4) The high-performance ceramic composite material disclosed in the present invention has higher bending strength, more sufficient fracture toughness, better wear resistance and longer service life through reasonable selection of preparation process parameters. DETAILED DESCRIPTION

[0032] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0033] Embodiment 1, a high-performance ceramic composite material, comprising the following components in parts by weight: 15 parts of nanofiber material, 3 parts of graphene, 60 parts of ceramic matrix, 8 parts of other nanomaterials, and 1 part of additive; the ceramic matrix is ​​Zr-Al-Ba-Ge-rare earth element-MQO, wherein M is Ti; the Q is a mixture of B and Si in a mass ratio of 1:0.8; the additive comprises the following raw materials in parts by weight: 3 parts of amphoteric organic ion salt, 1 part of benzene ring-containing hyperbranched polyborosilazane, and 0.2 parts of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole.

[0034] The amphoteric organic ion salt is hydroxypropane sulfonic acid pyridinium salt; the benzene ring-containing hyperbranched polyborosilazane is prepared according to the method in the Chinese invention patent with application announcement number CN117024144A; the preparation method of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole, see: Guo Yong, Shao Shijun, He Lijun, et al. Synthesis and Characterization of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole [J]. Chemical Reagents, 2002 (6): 344-345; the rare earth element is Y, Ce, and Gd mixed in a mass ratio of 1:1:0.3; the other nanomaterials are nano-aluminum nitride, nano-chromium boride, nano-hafnium silicide, and nano-molybdenum carbide mixed in a mass ratio of 1:1:0.8:1; the particle size of the other nanomaterials is 20nm.

[0035] The preparation method of the ceramic matrix comprises the following steps: dispersing a zirconium source, an aluminum source, a barium source, a germanium source, a rare earth source, an M source, and a Q source in an alcohol solvent, stirring evenly, slowly adding sodium acetate to obtain a mixture, transferring the mixture to a hydrothermal reactor lined with polytetrafluoroethylene, and reacting at 200° C. for 15 hours; cooling to room temperature, repeatedly washing with anhydrous ethanol, drying to constant weight in a vacuum drying oven at 85° C., roasting, and grinding through a 300-mesh sieve to obtain a ceramic matrix; The zirconium source is zirconium chloride; the aluminum source is aluminum chloride; the barium source is barium chloride; the germanium source is germanium chloride; the rare earth source includes yttrium nitrate, cerium nitrate, and gadolinium chloride; the M source is titanium nitrate; the Q source includes sodium borate and silicon tetrachloride; the zirconium source, aluminum source, barium source, germanium source, rare earth source, M source, Q source, alcohol solvent, and sodium acetate are in a ratio of 1:0.4:0.05:0.08:0.1:0.12:0.03:10:3; the alcohol solvent is ethanol.

[0036] The graphene is a single-layer graphene powder with a sheet diameter of 0.5 μm and a thickness of 0.8 nm; the nanofiber material is nano-boron fiber; the nanofiber material has an average diameter of 20 nm and a length of 10 μm.

[0037] A method for preparing the high performance ceramic composite material comprises the following steps:

[0038] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0039] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;

[0040] Step S3: sintering the green body to obtain a high-performance ceramic composite material.

[0041] The drying in step S2 is carried out under vacuum, the drying time is 15 hours, and the drying temperature is 85°C; the screening in step S2 is through a 100-mesh sieve; the debinding is carried out under vacuum, the debinding temperature is 440°C, and the debinding time is 2 hours; the shaping pressure is 12MPa, the temperature is 200°C, and the insulation time is 2 hours; the sintering treatment conditions in step S3 are: heating rate 6°C / min, sintering temperature 1550°C, and insulation time 5 hours.

[0042] Example 2, a high-performance ceramic composite material, comprising the following components in parts by weight: 17 parts of nanofiber material, 3.5 parts of graphene, 65 parts of ceramic matrix, 9 parts of other nanomaterials, and 1.5 parts of additives; the ceramic matrix is ​​Zr-Al-Ba-Ge-rare earth element-MQO, wherein M is Ta; Q is a mixture of B and Si in a mass ratio of 1:0.9; the additive comprises the following raw materials in parts by weight: 4 parts of amphoteric organic ion salt, 1.2 parts of benzene ring-containing hyperbranched polyborosilazane, and 0.25 parts of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole.

[0043] The amphoteric organic ion salt is 1-benzylpyridine-3-carboxylate; the benzene ring-containing hyperbranched polyborosilazane is prepared according to the method in the Chinese invention patent application announcement number CN117024144A; the preparation method of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole, see: Guo Yong, Shao Shijun, He Lijun, et al. Synthesis and Characterization of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole [J]. Chemical Reagents, 2002 (6): 344-345; the rare earth element is Y, Ce, Gd mixed in a mass ratio of 1:1.2:0.35; the other nanomaterials are nano-aluminum nitride, nano-chromium boride, nano-hafnium silicide, and nano-molybdenum carbide mixed in a mass ratio of 1:1.2:0.9:1.2; the particle size of the other nanomaterials is 30nm.

[0044] The preparation method of the ceramic matrix comprises the following steps: dispersing a zirconium source, an aluminum source, a barium source, a germanium source, a rare earth source, an M source and a Q source in an alcohol solvent, stirring evenly, slowly adding sodium acetate to obtain a mixture, transferring the mixture to a hydrothermal reactor lined with polytetrafluoroethylene, reacting at 205°C for 17 hours; cooling to room temperature, repeatedly washing with anhydrous ethanol, drying to constant weight in a vacuum drying oven at 87°C, roasting, grinding and passing through a 350-mesh sieve to obtain a ceramic matrix; The zirconium source is zirconium nitrate; the aluminum source is aluminum nitrate; the barium source is barium nitrate; the germanium source is germanium chloride; the rare earth source includes yttrium nitrate, cerium nitrate, and gadolinium chloride; the M source is tantalum ethoxide; the Q source includes sodium borate and silicon tetrachloride; the zirconium source, aluminum source, barium source, germanium source, rare earth source, M source, Q source, alcohol solvent, and sodium acetate are in a ratio of 1:0.45:0.05:0.09:0.1:0.12:0.03:13:3; the alcohol solvent is ethylene glycol.

[0045] The graphene is a single-layer graphene powder with a sheet diameter of 2 μm and a thickness of 0.9 nm; the nanofiber material is carbon nanofiber; the nanofiber material has an average diameter of 40 nm and a length of 15 μm.

[0046] A method for preparing the high performance ceramic composite material comprises the following steps:

[0047] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0048] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;

[0049] Step S3: sintering the green body to obtain a high-performance ceramic composite material.

[0050] The drying in step S2 is carried out under vacuum, the drying time is 18 hours, and the drying temperature is 88°C; the screening in step S2 is through a 150-mesh sieve; the debinding is carried out under a vacuum environment, the debinding temperature is 480°C, and the debinding time is 2.5 hours; the shaping pressure is 14MPa, the temperature is 230°C, and the insulation time is 2.3 hours; the sintering treatment conditions in step S3 are: heating rate 7°C / min, sintering temperature 1620°C, and insulation time 7h.

[0051] Embodiment 3, a high-performance ceramic composite material, comprising the following components in parts by weight: 20 parts of nanofiber material, 4 parts of graphene, 70 parts of ceramic matrix, 10 parts of other nanomaterials, and 2 parts of additives; the ceramic matrix is ​​Zr-Al-Ba-Ge-rare earth element-MQO, wherein M is Hf; the Q is a mixture of B and Si in a mass ratio of 1:1; the additive comprises the following raw materials in parts by weight: 4.5 parts of amphoteric organic ion salt, 1.5 parts of benzene ring-containing hyperbranched polyborosilazane, and 0.3 parts of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole.

[0052] The amphoteric organic ion salt is hydroxypropane sulfonic acid pyridinium salt; the benzene ring-containing hyperbranched polyborosilazane is prepared according to the method in the Chinese invention patent with application announcement number CN117024144A; the preparation method of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole, see: Guo Yong, Shao Shijun, He Lijun, et al. Synthesis and Characterization of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole [J]. Chemical Reagents, 2002 (6): 344-345; the rare earth element is Y, Ce, Gd mixed in a mass ratio of 1:1.5:0.4; the other nanomaterials are nano-aluminum nitride, nano-chromium boride, nano-hafnium silicide, and nano-molybdenum carbide mixed in a mass ratio of 1:1.5:1:1.3; the particle size of the other nanomaterials is 70nm.

[0053] The preparation method of the ceramic matrix comprises the following steps: dispersing a zirconium source, an aluminum source, a barium source, a germanium source, a rare earth source, an M source and a Q source in an alcohol solvent, stirring evenly, slowly adding sodium acetate to obtain a mixture, transferring the mixture to a hydrothermal reactor lined with polytetrafluoroethylene, and reacting at 210°C for 19 hours; cooling to room temperature, repeatedly washing with anhydrous ethanol, drying to constant weight in a vacuum drying oven at 90°C, roasting, grinding and passing through a 400-mesh sieve to obtain a ceramic matrix; the zirconium source is zirconium chloride; the aluminum source is aluminum nitrate; the barium source is barium chloride; the germanium source is germanium chloride; the rare earth source includes yttrium nitrate, cerium nitrate and gadolinium chloride; the M source is hafnium tetranitrate; the Q source includes sodium borate and silicon tetrachloride; the zirconium source, aluminum source, barium source, germanium source, rare earth source, M source, Q source, alcohol solvent and sodium acetate are in a ratio of 1:0.5:0.05: 0.1:0.1:0.12:0.03:15:3; the alcohol solvent is n-butanol.

[0054] The graphene is a single-layer graphene powder with a sheet diameter of 3.5 μm and a thickness of 1 nm; the nanofiber material is nano-boron fiber; the nanofiber material has an average diameter of 80 nm and a length of 20 μm.

[0055] A method for preparing the high performance ceramic composite material comprises the following steps:

[0056] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0057] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;

[0058] Step S3: sintering the green body to obtain a high-performance ceramic composite material.

[0059] The drying in step S2 is carried out under vacuum, the drying time is 20 hours, and the drying temperature is 90°C; the screening in step S2 is through a 200-mesh sieve; the debinding is carried out under vacuum, the debinding temperature is 510°C, and the debinding time is 3 hours; the shaping pressure is 16MPa, the temperature is 260°C, and the insulation time is 2.5 hours; the sintering treatment conditions in step S3 are: heating rate 8°C / min, sintering temperature 1800°C, and insulation time 8 hours.

[0060] Embodiment 4, a high-performance ceramic composite material, comprising the following components in parts by weight: 23 parts of nanofiber material, 4.5 parts of graphene, 75 parts of ceramic matrix, 11 parts of other nanomaterials, and 2.5 parts of additives; the ceramic matrix is ​​Zr-Al-Ba-Ge-rare earth element-MQO, wherein M is Nb; the Q is a mixture of B and Si in a mass ratio of 1:1.1; the additive comprises the following raw materials in parts by weight: 5.5 parts of amphoteric organic ion salt, 1.8 parts of benzene ring-containing hyperbranched polyborosilazane, and 0.35 parts of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole.

[0061] The amphoteric organic ion salt is a mixture of hydroxypropane sulfonic acid pyridinium salt and 1-benzylpyridine-3-carboxylate in a mass ratio of 3:5; the benzene ring-containing hyperbranched polyborosilazane is prepared according to the method in the Chinese invention patent application announcement number CN117024144A; the preparation method of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole, see: Guo Yong, Shao Shijun, He Lijun, et al. Synthesis and Characterization of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole [J]. Chemical Reagents, 2002 (6): 344-345; the rare earth element is a mixture of Y, Ce, and Gd in a mass ratio of 1:1.8:0.45; the other nanomaterials are a mixture of nano aluminum nitride, nano chromium boride, nano hafnium silicide, and nano molybdenum carbide in a mass ratio of 1:1.8:1.1:1.4; the particle size of the other nanomaterials is 80nm.

[0062] The preparation method of the ceramic matrix comprises the following steps: dispersing a zirconium source, an aluminum source, a barium source, a germanium source, a rare earth source, an M source and a Q source in an alcohol solvent, stirring evenly, slowly adding sodium acetate to obtain a mixture, transferring the mixture to a hydrothermal reactor lined with polytetrafluoroethylene, and reacting at 215°C for 21 hours; cooling to room temperature, repeatedly washing with anhydrous ethanol, drying to constant weight in a vacuum drying oven at 93°C, roasting, and grinding through a 450-mesh sieve to obtain a ceramic matrix; the zirconium source is a mixture of zirconium chloride and zirconium nitrate in a mass ratio of 3:5; the aluminum source is aluminum chloride, aluminum nitrate, and aluminum nitrate; The barium source is a mixture of barium chloride and barium nitrate in a mass ratio of 3:5; the germanium source is germanium chloride; the rare earth source includes yttrium nitrate, cerium nitrate, and gadolinium chloride; the M source is niobium pentachloride; the Q source includes sodium borate and silicon tetrachloride; the zirconium source, aluminum source, barium source, germanium source, rare earth source, M source, Q source, alcohol solvent, and sodium acetate are 1:0.55:0.05:0.11:0.1:0.12:0.03:18:3; the alcohol solvent is a mixture of ethanol, ethylene glycol, and n-butanol in a mass ratio of 1:1:2.

[0063] The graphene is a single-layer graphene powder with a sheet diameter of 4.5 μm and a thickness of 1.1 nm; the nanofiber material is a mixture of nano-boron fiber and carbon nanofiber in a mass ratio of 1:2; the average diameter of the nanofiber material is 90 nm and the length is 25 μm.

[0064] A method for preparing the high performance ceramic composite material comprises the following steps:

[0065] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0066] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;

[0067] Step S3: sintering the green body to obtain a high-performance ceramic composite material.

[0068] The drying in step S2 is carried out under vacuum, the drying time is 23 hours, and the drying temperature is 93°C; the screening in step S2 is through a 250-mesh sieve; the debinding is carried out under a vacuum environment, the debinding temperature is 540°C, and the debinding time is 3.5 hours; the shaping pressure is 17MPa, the temperature is 290°C, and the insulation time is 2.9 hours; the sintering treatment conditions in step S3 are: heating rate 9.5°C / min, sintering temperature 1900°C, and insulation time 11h.

[0069] Example 5, a high-performance ceramic composite material, comprising the following components in parts by weight: 25 parts of nanofiber material, 5 parts of graphene, 80 parts of ceramic matrix, 12 parts of other nanomaterials, and 3 parts of additives; the ceramic matrix is ​​Zr-Al-Ba-Ge-rare earth element-MQO, wherein M is Ti; the Q is a mixture of B and Si in a mass ratio of 1:1.2; the additive comprises the following raw materials in parts by weight: 6 parts of amphoteric organic ion salt, 2 parts of benzene ring-containing hyperbranched polyborosilazane, and 0.4 parts of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole.

[0070] The amphoteric organic ion salt is hydroxypropane sulfonic acid pyridinium salt; the benzene ring-containing hyperbranched polyborosilazane is prepared according to the method in the Chinese invention patent with application announcement number CN117024144A; the preparation method of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole, see: Guo Yong, Shao Shijun, He Lijun, et al. Synthesis and Characterization of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole [J]. Chemical Reagents, 2002 (6): 344-345; the rare earth element is Y, Ce, Gd mixed in a mass ratio of 1:2:0.5; the other nanomaterials are nano-aluminum nitride, nano-chromium boride, nano-hafnium silicide, and nano-molybdenum carbide mixed in a mass ratio of 1:2:1.2:1.5; the particle size of the other nanomaterials is 90nm.

[0071] The preparation method of the ceramic matrix comprises the following steps: dispersing a zirconium source, an aluminum source, a barium source, a germanium source, a rare earth source, an M source, and a Q source in an alcohol solvent, stirring evenly, slowly adding sodium acetate to obtain a mixture, transferring the mixture to a hydrothermal reactor lined with polytetrafluoroethylene, and reacting at 220° C. for 22 hours; cooling to room temperature, repeatedly washing with anhydrous ethanol, drying in a vacuum drying oven at 95° C. to constant weight, and grinding through a 500-mesh sieve after roasting to obtain a ceramic matrix; The zirconium source is zirconium chloride; the aluminum source is aluminum nitrate; the barium source is barium chloride; the germanium source is germanium chloride; the rare earth source includes yttrium nitrate, cerium nitrate, and gadolinium chloride; the M source is titanium nitrate; the Q source includes sodium borate and silicon tetrachloride; the zirconium source, aluminum source, barium source, germanium source, rare earth source, M source, Q source, alcohol solvent, and sodium acetate are in a ratio of 1:0.6:0.05:0.12:0.1:0.12:0.03:20:3; the alcohol solvent is ethanol.

[0072] The graphene is a single-layer graphene powder with a sheet diameter of 5 μm and a thickness of 1.2 nm; the nanofiber material is nano-boron fiber; the nanofiber material has an average diameter of 100 nm and a length of 30 μm.

[0073] A method for preparing the high performance ceramic composite material comprises the following steps:

[0074] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0075] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;

[0076] Step S3: sintering the green body to obtain a high-performance ceramic composite material.

[0077] The drying in step S2 is carried out under vacuum, the drying time is 24 hours, and the drying temperature is 95°C; the screening in step S2 is through a 300-mesh sieve; the debinding is carried out under vacuum, the debinding temperature is 550°C, and the debinding time is 4 hours; the shaping pressure is 18MPa, the temperature is 300°C, and the insulation time is 3 hours; the sintering treatment conditions in step S3 are: heating rate 10°C / min, sintering temperature 1950°C, and insulation time 12h.

[0078] Comparative Example 1, a high-performance ceramic composite material and a preparation method thereof, is substantially the same as Example 1, except that graphene and amphoteric organic ion salt are not added.

[0079] Comparative Example 2, a high-performance ceramic composite material and a preparation method thereof, is substantially the same as Example 1, except that Meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole and other nanomaterials are not added.

[0080] In order to further illustrate the beneficial technical effects of the high-performance ceramic composite materials involved in each embodiment of the present invention, relevant performance tests were performed on the high-performance ceramic composite materials involved in Examples 1-5 and Comparative Examples 1-2; the test methods are as follows:

[0081] (1) Flexural strength: Refer to GB / T 4741-1999 for flexural strength test.

[0082] (2) Wear resistance: Wear resistance is expressed by linear wear rate, which is tested by MM-1000 friction tester. The test conditions are: inertia 3.8kgf•cm•s2, specific pressure 100N / cm2, linear speed 25m / s.

[0083] (3) Fracture toughness: The test was carried out according to the three-point bending test of GB / T 23806-2009. The test results are shown in Table 1.

[0084]

[0085] As can be seen from Table 1, the high-performance ceramic composite materials involved in each embodiment of the present invention have better flexural strength, wear resistance and fracture toughness than the comparative example products. The combined use of graphene, amphoteric organic ion salts, Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole and other nanomaterials is beneficial to improving the above properties.

[0086] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A high performance ceramic composite material, characterized in that: The invention comprises the following components in parts by weight: 15-25 parts of nanofiber material, 3-5 parts of graphene, 60-80 parts of ceramic matrix, 8-12 parts of other nanomaterials, and 1-3 parts of auxiliary agent; the ceramic matrix is ​​Zr-Al-Ba-Ge-rare earth element-MQO, wherein M is at least one of Ti, Ta, Hf, and Nb; Q is a mixture of B and Si in a mass ratio of 1:(0.8-1.2); the auxiliary agent comprises the following raw materials in parts by weight: 3-6 parts of amphoteric organic ion salt, 1-2 parts of benzene ring-containing hyperbranched polyborosilazane, and 0.2-0.4 parts of Meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole; The amphoteric organic ion salt is at least one of hydroxypropane sulfonate pyridinium salt and 1-benzylpyridine-3-carboxylate; the rare earth element is Y, Ce, and Gd mixed in a mass ratio of 1:(1-2):(0.3-0.5); the other nanomaterials are nano-aluminum nitride, nano-chromium boride, nano-hafnium silicide, and nano-molybdenum carbide mixed in a mass ratio of 1:(1-2):(0.8-1.2):(1-1.5); the particle size of the other nanomaterials is 20-90nm; The preparation method of the ceramic matrix comprises the following steps: dispersing a zirconium source, an aluminum source, a barium source, a germanium source, a rare earth source, an M source and a Q source in an alcohol solvent, stirring evenly, slowly adding sodium acetate to obtain a mixture, transferring the mixture to a hydrothermal reactor lined with polytetrafluoroethylene, and reacting at 200-220°C for 15-22h; cooling to room temperature, repeatedly washing with anhydrous ethanol, drying to constant weight in a vacuum drying oven at 85-95°C, calcining, and grinding through a 300-500 mesh sieve to obtain a ceramic matrix; the zirconium source is at least one of zirconium chloride and zirconium nitrate; the aluminum source is is at least one of aluminum chloride and aluminum nitrate; the barium source is at least one of barium chloride and barium nitrate; the germanium source is germanium chloride; the rare earth source includes yttrium nitrate, cerium nitrate, and gadolinium chloride; the M source is at least one of titanium nitrate, tantalum ethoxide, hafnium tetranitrate, and niobium pentachloride; the Q source includes sodium borate and silicon tetrachloride; the ratio of the zirconium source, aluminum source, barium source, germanium source, rare earth source, M source, Q source, alcohol solvent, and sodium acetate is 1:(0.4-0.6):0.05:(0.08-0.12):0.1:0.12:0.03:(10-20):3; The sintering treatment conditions of the high-performance ceramic composite material are: heating rate 6-10° C. / min, sintering temperature 1550-1950° C., and holding time 5-12 h.

2. The high performance ceramic composite material according to claim 1, characterized in that: The alcohol solvent is at least one of ethanol, ethylene glycol and n-butanol.

3. The high performance ceramic composite material according to claim 1, characterized in that: The graphene is a single-layer graphene powder with a sheet diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm; the nanofiber material is at least one of nano-boron fiber and carbon nanofiber; the average diameter of the nanofiber material is 20-100 nm and the length is 10-30 μm.

4. A method for preparing a high-performance ceramic composite material according to any one of claims 1 to 3, characterized in that: The steps include: Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder; Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body; Step S3: sintering the green body to obtain a high-performance ceramic composite material.

5. The method for preparing the high performance ceramic composite material according to claim 4, characterized in that: The drying in step S2 is carried out under vacuum, the drying time is 15-24 hours, and the drying temperature is 85-95°C; the screening in step S2 is through a 100-300 mesh sieve; the debinding is carried out under vacuum, the debinding temperature is 440-550°C, and the debinding time is 2-4 hours; the shaping pressure is 12-18MPa, the temperature is 200-300°C, and the insulation time is 2-3 hours.

Citation Information

Patent Citations

  • Benzene ring-containing hyperbranched polyborosilazane converted amorphous SiBCN wave-absorbing ceramic and preparation method thereof

    CN117024144A

  • Preparation method of ceramic-based composite material

    CN117945770A

  • SiBCN metal-free ceramic wave-absorbing material obtained from cracking conversion of benzene ring-containing polymer and preparation method thereof

    CN109251038A

  • Aluminum nitride reinforced aluminum-based composite material and preparation method thereof

    CN118109723A